Influence of nickel on the susceptibility to corrosion fatigue of duplex stainless steel welds - Tavara, S. A. (2001)
The object of this work is to analyse the mechanisms of corrosion fatigue and to study the influence of Nickel on the susceptibility to corrosion fatigue in welded Duplex stainless steels. A ‘Ferralium 255’ type cast Duplex stainless steel was used as base material. Four types of experimental electrodes of chemical composition similar to base material were used, with varying compositions of Ni (2.8, 4.7, 6.8 and 9.8 wt%). Experimental three point bending fatigue tests were carried out in air at 10 Hz, and in normalised seawater at 3 Hz, with anodic polarisation to 800 mV ECS. The strain gauge technique was used to monitor subcritical propagation of cracks. The effect of the corrosive environment on crack growth rates and on the coefficients of the Paris equation were assessed for each type of electrode. Comparing the experimental results, it was determined that the best electrode is the one that contains 4.7% Ni.